Resistência ao Tomato Severe Rugose Virus (ToSRV) em híbridos de tomateiro com diferentes constituições genotípicas no loco TY-1 - Brioschi, Keila de Cássia (2016)
With this work, we aimed at comparing the effect of different genotypic constitutions on locus Ty-1 (resistant heterozygous, resistant homozygous and susceptible homozygous), in relation to the resistance level of tomato hybrids to the Tomato Severe Rugose Virus (ToSRV). We also aimed at detecting possible effects of the Mi allele in the increment of resistance to begomovirus ToSRV, in addition to identifying if the form of the fruit (round or saladete) is associated to higher resistance to the virus. An experiment was conducted with 28 genotypes, 4 commercial hybrids and 24 obtained hybrids, with different fruit forms and different genotypic constitutions in the locus Ty-1 and Mi. After inoculating the plants with ToSRV, by means of virulent whitefly (Biotype B Bemisia tabaci), the experiment was conducted in greenhouse at the Bayer Vegetable Seeds research center, using a randomized blocks design comprised of 28 treatments, with four replicates and 10 plants per plot, totalizing 1120 plants. The results obtained from the hybrid resistance test to ToSRV confirmed the efficiency of gene Ty-1 in controlling the symptoms in heterozygosis and homozygosis, with the allele in homozygosis is more effective. Allele Mi in heterozygosis was not effective in incrementing the level of resistance to the virus, and the form of the fruit did not interfere in the level of resistance to ToSRV.